The dynamics of Chinese rural households' participation in labor markets - Stephan Brosig; Thomas Glauben; Thomas Herzfeld; Scott Rozelle; Xiaobing Wang (Agricultural Economics, 2007)
The work is devoted to the dynamics of labor market participation of Chinese rural households. Based on a theoretical farm household framework the choice between four distinct labor market participation states is empirically analyzed. Using household data over the period 1995–2002 from the province Zhejiang we apply a discrete time hazard approach to analyze households' labor market participation histories. In particular, we investigate the movements between autarky and participation in general and, more specifically, the shifts between part-time and full-time farming. Estimation results suggest significant duration dependence, more precisely, a decreasing risk of moving from one state to another with an increasing time a household occupies one of these states. Further, the likelihoods of starting any participation in labor markets and to start part-time farming are considerably higher than to end participation or to return to full-time farming. In addition, we find that labor market participation decisions are significantly related to several household and farm characteristics.
Keywords: C41; J22; J24; J43; J62; Q12; 330